Medicinal uses of agarwood - Lertnimitphun Peeraphong (Wolters Kluwer Health/LWW, 2021)
Agarwood from Aquilaria plants, also known as Chen Xiang (沉香), is traditionally used for the treatment of abdominal pain and as a sedative. Because of the great demand and the rareness of agarwood, extensive harvesting of Aquilaria plants has nearly led to the extinction of the species. To fully utilize this resource, the use of different parts of Aquilaria needs to be investigated. This article will focus on the pharmacological properties and the mechanism of action of different parts of Aquilaria plants.